Introduction to aluminum alloys and tempers - Kaufman, J. G. 1931- (ASM International, 2000)
Annotation Examines characteristics of wrought and cast aluminum alloys, then presents basic aluminum alloy and temper designation systems, as developed by the Aluminum Association, and explains them with examples. Wrought and cast aluminum designations are treated in a similar fashion. Processes used to produce aluminum alloy products are described briefly, and representative applications for aluminum alloys and tempers are detailed, in areas such as electrical markets, building and construction, marine and rail transportation, packaging, and petroleum and chemical industry components. A final chapter presents 65 pages of bandw micrographs illustrating the microstructure of a range of aluminum alloys and tempers, to assist in understanding consequences of applying the production technology implied by the temper designations. Annotation copyrighted by Book News, Inc., Portland, OR.
Keywords: Aluminum alloys.; Metals -- Heat treatment.; elektronické knihy; electronic books